2005
DOI: 10.2174/0929867054039044
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Treatment of Autoimmune Diseases; Cellular Activity, Type-1/Type-2 Cytokine Secretion Patterns and their Modulation by Therapeutic Peptides

Abstract: Autoimmune diseases are many, have an overall prevalence of about 3% of the world population, affecting more women than men, and their incidence is influenced by genetics and the environment. It is currently thought that the immune response of a genetically predisposed individual to an environmental pathogen, under the influence of inadequate or non-functional immunoregulatory mechanisms, can lead to the development of an autoimmune disease. Advances in the treatment of autoimmune diseases follow a better unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 167 publications
0
5
0
Order By: Relevance
“…This molecule, which is a natural product of cell types such as several cells of the innate immune system, endothelial cells, and epithelial cells, acts as a ligand to the inhibitory molecule Tim-3. Tim-3 is expressed on the surface of both Th17 cells and Th1 cells which are critically involved in initiation of inflammatory and autoimmune disease [41]. Zhu et al , have revealed that the Tim-3-galectin-9 pathway has evolved to ensure effective termination of effector Th1 cells [20].…”
Section: Resultsmentioning
confidence: 99%
“…This molecule, which is a natural product of cell types such as several cells of the innate immune system, endothelial cells, and epithelial cells, acts as a ligand to the inhibitory molecule Tim-3. Tim-3 is expressed on the surface of both Th17 cells and Th1 cells which are critically involved in initiation of inflammatory and autoimmune disease [41]. Zhu et al , have revealed that the Tim-3-galectin-9 pathway has evolved to ensure effective termination of effector Th1 cells [20].…”
Section: Resultsmentioning
confidence: 99%
“…This decrease in nitrotyrosine levels is consistent with previous observation of nitrotyrosine clearance from the central nervous system tissue of mice with EAE that are undergoing treatment with UA. 10 In addition, we detected evidence of increased Th2 activity in the peripheral blood of this individual that has previously been reported as beneficial in patients with MS. 29 Mechanistically, the principal therapeutic effects of inosine treatment are likely through raising serum UA levels, thereby reducing the pathological effects of peroxynitritedependent radicals. Radical-mediated oxidative stress may lead to the neuronal and oligodendrocyte loss that underlies the degenerative component of MS.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, induction of Th2 populations, which are associated with the transcription factor GATA-3 and cytokines such as IL-4 and -10, results in a dominant protective effect against autoimmunity in this model ( 1 ). This paradigm is not specific to type 1 diabetes; in fact, the relative pathogenic contributions of Th1 cells and protective effects of Th2 cells have been described as a common feature of other organ-specific autoimmune diseases, including multiple sclerosis and rheumatoid arthritis ( 2 – 4 ).…”
mentioning
confidence: 99%